IoT-BASED TELEMEDICINE SYSTEM TO ADDRESS HEALTHCARE ACCESS CHALLENGES IN NIGERIA - Kyado, Doris Jonah; Iliya, Apuru Jonathan; Mohammed, Tirmizi; Kenneth, Shiaki Nzukwen (FUDMA JOURNAL OF SCIENCES, 2025)
The Internet of Things (IoT) integrates sensors, software, and connectivity to enable real-time data exchange between devices and systems, playing a transformative role in modern telemedicine. This study presents an IoT-based telemedicine system developed to address healthcare access challenges in Nigeria, especially in rural and underserved areas. The system includes an Android mobile application that uses the smartphone’s camera to capture pulse readings, enabling preliminary assessment of patients' cardiac health. In parallel, a web-based administrative platform allows healthcare administrators to register medical practitioners, assign doctors to patients, schedule consultations, and manage cloud-based patient records. To protect sensitive health data, the system implements the Advanced Encryption Standard (AES) for secure data encryption and decryption. Developed using Flutter SDK, Dart programming language, Visual Studio Code, and Firebase, the application—referred to as the Rim360 Health App—demonstrates how IoT can facilitate real-time, encrypted patient monitoring and doctor-patient interaction. The system holds potential to significantly enhance telemedicine adoption in Nigeria by providing accessible, secure, and scalable healthcare solutions for remote populations.
Keywords: Android; Cloud-Computing; Diagnosis; Internet of Things; Telemedicine